Assessment of adherence to psychotropic medications among outâ€patients at the Pharmacy Department of a Psychiatric Hospital, in Benin City, Nigeria - Odo, Hillary O. (Asian Journal of Pharmaceutics (AJP), 2014)
Patient adherence to medication regimens determines the success of the illness remission. Poorâ€adherence amongÂ patients diagnosed with psychiatric illnesses is associated with poor clinical outcomes and high economic and humanÂ resource utilization.The aim was to evaluate the level of patientsâ€™ adherence to psychotropic drugs and also to explore factorsÂ associated with poor medication adherence. A crossâ€sectional questionnaire survey of 200 (n = 200) conveniently sampledÂ patients in an outâ€patient pharmacy setting using a sociodemographic questionnaire and the eightâ€item Morisky medicationÂ adherence scale. Descriptive and inferential statistics were used to summarize and test for associations in the variables. Adherence varied from poorâ€adherence (55.5%) through moderate (36%) to high adherence (8.5%) among participants.Â No significant associations were observed between poor medication adherence and the socioâ€demographic characteristicsÂ of patients. More than half of the psychiatric outâ€patients were poorly adherent to prescribed medications. Strategies toÂ improve adherence are crucial in psychiatric care. Key words: Medication adherence, outâ€patients, pharmacy, psychiatry, psychotropic